2017
DOI: 10.1021/acs.jmedchem.7b01070
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships of Potent, Targeted Covalent Inhibitors That Abolish Both the Transamidation and GTP Binding Activities of Human Tissue Transglutaminase

Abstract: Human tissue transglutaminase (hTG2) is a multifunctional enzyme. It is primarily known for its calcium-dependent transamidation activity that leads to formation of an isopeptide bond between glutamine and lysine residues found on the surface of proteins, but it is also a GTP binding protein. Overexpression and unregulated hTG2 activity have been associated with numerous human diseases, including cancer stem cell survival and metastatic phenotype. Herein, we present a series of targeted covalent inhibitors (TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(108 citation statements)
references
References 75 publications
2
98
0
Order By: Relevance
“…NC9 is a TG2-selective irreversible inhibitor that blocks the enzyme active site and locks TG2 in an open conformation, thereby abrogating GTP binding as well. [11,17]. Our results showed that inhibition of TG2 by NC9 in ATRA + ATO combined treatment significantly reduces not just reactive oxygen species (ROS) but also proinflammatory cytokines and chemokine production that significantly increases the severity of DS.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…NC9 is a TG2-selective irreversible inhibitor that blocks the enzyme active site and locks TG2 in an open conformation, thereby abrogating GTP binding as well. [11,17]. Our results showed that inhibition of TG2 by NC9 in ATRA + ATO combined treatment significantly reduces not just reactive oxygen species (ROS) but also proinflammatory cytokines and chemokine production that significantly increases the severity of DS.…”
Section: Introductionmentioning
confidence: 72%
“…The pro-apoptotic effects of TG2 are associated with the calcium-dependent protein-protein cross-linking activity at high calcium levels. In its survival-promoting attribution, TG2 most often participates as a protein-protein interaction partner in GTP-bound form [17,18]. In earlier studies, others tested a novel irreversible TG2 inhibitor NC9 to identify agents that can selectively target cancer stem cells in tumors [13,19,20].…”
mentioning
confidence: 99%
“…The Keillor group recently reported the TGase 2 inhibitor VA4, optimized from hit compound NC9. This inhibitor blocks the transamidation activity of TGase 2, as well as its GTP binding ability, through an allosteric mechanism [72]. VA4 was reported to be the best lead compound among the sulfonamide and piperazinyl amide derivatives designed to interact with the active site of TGase 2 [72].…”
Section: Anti-cancer Effect Of Tgase 2 Inhibition In Ccrccmentioning
confidence: 99%
“…This inhibitor blocks the transamidation activity of TGase 2, as well as its GTP binding ability, through an allosteric mechanism [72]. VA4 was reported to be the best lead compound among the sulfonamide and piperazinyl amide derivatives designed to interact with the active site of TGase 2 [72]. We investigated whether these specific irreversible inhibitors for TGase 2 might also block TGase 2-p53 binding and p53 depletion in RCC cells.…”
Section: Anti-cancer Effect Of Tgase 2 Inhibition In Ccrccmentioning
confidence: 99%
“…Although direct measurements of TG2 intracellular conformation have not been performed in unperturbed gastric cancer cells, indirect data suggests that TG2 exists in the closed GTP bound form in these cells where it is expected to drive cancer cell survival signaling (Figure A). This suggests that TG2 inhibitors, which suppress GTP binding by indirectly disordering the TG2 GTP binding site, may be a useful treatment for gastric cancer.…”
Section: Tg2 In Tumor Typesmentioning
confidence: 99%